2010
DOI: 10.1126/science.1192912
|View full text |Cite
|
Sign up to set email alerts
|

ATM Activation by Oxidative Stress

Abstract: Stress, DNA Damage, and ATM The protein kinase ATM (ataxia-telangiectasia mutated) is a key component of the signaling pathway through which cells are protected from DNA damage. ATM becomes activated within a protein complex at sites of double-stranded breaks in DNA. ATM is also activated in response to increased production of reactive oxygen species (ROS). Such activation was thought to reflect DNA damage caused by ROS, but Guo et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

55
972
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 964 publications
(1,033 citation statements)
references
References 109 publications
(111 reference statements)
55
972
3
3
Order By: Relevance
“…It should be noted that ROS elicited by emodin may not upregualte p53 expression directly. In cancer cells excessive intercellular ROS often induces oxidative DNA damage, which activates ATM and subsequently promotes p53 expression (Guo et al, 2010;Huang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that ROS elicited by emodin may not upregualte p53 expression directly. In cancer cells excessive intercellular ROS often induces oxidative DNA damage, which activates ATM and subsequently promotes p53 expression (Guo et al, 2010;Huang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…38,39 It was shown that H 2 O 2 treatment induces phosphorylation of ATM (S1981) but not H2AXb. 38 Thus, ATM can be activated by a mechanism independent from DNA DSBs. We have examined the cellular redox status following Roc treatment in several tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, elevated oxidative stress has been identified in several DNA repair deficiencies, including A-T. 16 -22 Notably, ATM has recently been shown to be activated by oxidative stress. 23 Ocular tissues, especially the retina, are exposed to extremely high levels of reactive oxygen species. Nevertheless, retinal neurodegeneration has not been reported in A-T patients.…”
mentioning
confidence: 99%